Processes of Inquiry Inservice Teacher Educators Research Their Practice - Higgins, Joanna; Parsons, Ro.; Bonne, Linda; SpringerLink (Online service) (Rotterdam : SensePublishers, 2011)
This book presents inservice teacher educators$1 (Baccounts of systematic inquiry into their practice in a variety of contexts throughout New Zealand. The importance of purposeful networks of practice at all levels of a system in supporting education change and improvement is a theme across the chapters. The contributors describe the challenges and successes associated with working in professional learning and development in ways that aim to improve outcomes for teacher educators, teachers and students. Their accounts illuminate the importance of a research and development approach that enables the generation and application of new knowledge and, more importantly, enables all contributors to be learners. Each of the authors describes their role in investigating the effectiveness of inservice teacher educator practice, as part of the overall project that endeavoured to improve practice for the future. Included are processes created for Maori (indigenous) settings where cultural metaphors were used to frame investigations of practice. The book makes an important contribution to our knowledge base about effective inservice teacher educator practice and its influence on classroom practice. The book will appeal to teacher educators interested in examining the fit between their practices and their goals in helping teachers to build knowledge and practice, including those working in indigenous settings. It will also be of interest to policy makers and evaluators involved in system-level change. $1! =(Ba well organised and carefully argued text that offers compelling evidence for an integrated approach to project management, practice, research and evaluation (J. John Loughran, Series Editor).s
Keywords: Education; Education; Teaching and Teacher Education